Flame-retardant PMMA plate and preparation method thereof

By adding synergistic flame retardants and modified nano -silica to PMMA plates, the method of polymerization reaction and annealing treatment is used to solve the problem of poor thermal stability and abrasion resistance of PMMA plates, and achieve efficient flame retardant performance and Excellent mechanical performance.

CN119350539AActive Publication Date: 2025-01-24SHANGHAI PINCHENG HLDG GRP CO LTD

Patent Information

Application Number
CN202411944856.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-24
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing PMMA sheets have poor thermal stability and are easy to burn. Traditional flame retardants are easy to migrate and seep out in the material, affecting the flame retardant performance. The surface wear resistance of the sheet is average and cannot meet market demand.

Method used

A preparation method is used to add methyl acrylic, acrylic methyl ester, coordinated flame retardant, and modified nano -silica. PMMA plates with excellent abrasion and flame retardant properties are made through polymerization reactions and annealing treatment.

Benefits of technology

It significantly improves the flame retardancy and mechanical properties of PMMA sheets, enhances the wear resistance, solves the problems of flammability and insufficient wear resistance of traditional PMMA sheets, and meets higher market demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses a flame-retardant PMMA (polymethyl methacrylate) plate and a preparation method thereof, and belongs to the technical field of acrylic plates. Comprising the following raw materials in parts by weight: 70-80 parts of methyl methacrylate, 8-12 parts of methyl acrylate, 5-15 parts of a synergistic flame retardant, 10-18 parts of modified nano silicon dioxide, 0.2-0.4 part of an initiator and 3-5 parts of a release agent. Wherein the modified nano silicon dioxide is high in surface hydrophobicity and better in compatibility with a PMMA matrix, so that the wear resistance and the mechanical property of the PMMA plate are greatly enhanced; wherein the synergistic flame retardant can enhance the mechanical property of the PMMA plate, in addition, molecules contain three elements of silicon, nitrogen and phosphorus, and the three elements can achieve a synergistic effect, so that the flame retardance of the plate is remarkably improved, and the stability is good; therefore, the PMMA plate prepared by the invention is good in wear resistance and excellent in mechanical property, also has stable and efficient flame retardance, and has important application value in the technical field of acrylic plates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of acrylic plates, and in particular relates to a flame-retardant PMMA plate and a preparation method thereof. Background Art

[0002] Polymethyl methacrylate (PMMA), commonly known as organic glass or acrylic, is a non-crystalline plastic made of methyl methacrylate (MMA) monomer and a small amount of acrylic esters. It has high transparency, a transmittance of up to 92%, good optical properties, strong corrosion resistance, good resistance to ultraviolet rays and weather, suitable for outdoor use, and can maintain transparency for a long time. It is often used as a substitute for glass and has the reputation of "plastic glass". Due to its excellent performance, it is widely used in various fields, especially in construction. PMMA sheets are suitable for indoor lighting and safety needs due to their high transmittance and impact resistance. They are used to make doors, windows, partitions, lenses, etc.

[0003] With the expansion of material application fields and the continuous improvement of people's needs, PMMA materials are also facing flame retardant requirements. Since PMMA has poor thermal stability and is extremely easy to burn, the limiting oxygen index of pure PMMA is only 17, which greatly limits its application in more fields. By adding flame retardants, the flame retardant properties of PMMA materials can be effectively improved, but most traditional organic flame retardants are small molecules, which are easy to migrate and seep in PMMA materials, affecting the flame retardant properties of the materials; while inorganic flame retardants have poor compatibility with PMMA materials, and adding a large amount will affect the mechanical properties of the materials; not only that, the surface wear resistance of PMMA sheets is average, and scratches will occur during installation and use, affecting the appearance and light transmittance, so it cannot meet the existing market demand. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of acrylic board technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a flame retardant PMMA sheet and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing a flame retardant PMMA sheet comprises the following steps: First, methyl methacrylate, methyl acrylate, synergistic flame retardant and modified nano-silica are added to a reactor, and then an initiator and a release agent are added. Stirring is started and the temperature is increased. When the raw materials in the reactor are fully mixed and boiled, the temperature is kept for 20-40 minutes, and the heating is stopped. The slurry is allowed to stand and cool to obtain a slurry. The slurry is injected into a sealed glass mold, gas is removed, and polymerization reaction is caused by heating. After the reaction is completed, annealing treatment is carried out in an oven, and the mold is opened after cooling to room temperature. Finally, grinding and polishing are carried out to obtain a flame-retardant PMMA sheet.

[0006] Furthermore, the raw materials are calculated in parts by weight as follows: 70-80 parts of methyl methacrylate, 8-12 parts of methyl acrylate, 5-15 parts of synergistic flame retardant, 10-18 parts of modified nano-silica, 0.2-0.4 parts of initiator, and 3-5 parts of release agent.

[0007] Furthermore, the initiator is one of dibenzoyl peroxide and lauroyl peroxide.

[0008] Furthermore, the release agent is one of zinc stearate, magnesium stearate and montan wax.

[0009] Furthermore, the modified nano-silicon dioxide is prepared by the following steps: Disperse nano-silica in a three-necked flask filled with ethanol aqueous solution, add γ-methacryloxypropyltrimethoxysilane (silane coupling agent KH-570) after ultrasonic treatment for 10 minutes, gradually raise the temperature to 60°C, react for 5 hours under mechanical stirring, cool to room temperature after the reaction, take out the filter residue after filtration, wash it with anhydrous ethanol for 3-4 times, and dry it in a vacuum oven to obtain modified nano-silica.

[0010] Furthermore, the usage ratio of the nano-silica, the ethanol aqueous solution, and γ-methacryloxypropyltrimethoxysilane is 1 g:100 mL:3.4 g.

[0011] There are many -OH groups on the surface of nano-silica, which can introduce unsaturated carbon-carbon double bonds by reacting with the silane coupling agent KH-570: through this reaction, the hydrophobicity of the nano-silica surface can be improved, the compatibility of nano-silica with the PMMA matrix can be enhanced, and the nano-silica can be fully dispersed in the PMMA matrix, so that the performance of nano-silica can be fully exerted, greatly enhancing the wear resistance and mechanical properties of the matrix.

[0012] Furthermore, the synergistic flame retardant is prepared by the following steps: S1. In a four-necked flask equipped with a constant pressure dropping funnel, a stirrer, a thermometer, a nitrogen inlet and outlet, a reflux condenser and a drying tube (connected to a hydrogen chloride absorption device), add pentaerythritol and tetrahydrofuran, introduce nitrogen as a protective gas, start stirring, slowly heat up to 60°C, and drop phosphorus oxychloride. When the reaction starts, a large amount of gas is released, and the reaction system gradually changes from a white turbid liquid to a transparent one, and then gradually becomes turbid again until the addition of phosphorus oxychloride is completed. The temperature is raised to 70°C, and the reaction is refluxed for 4 hours. After the reaction is completed, the solvent is removed by distillation under reduced pressure, and the mixture is washed with anhydrous ethanol and chloroform in sequence, and dried to obtain intermediate 1; the ratio of pentaerythritol, tetrahydrofuran and phosphorus oxychloride is 15.1g:100mL:14.3g; Pentaerythritol reacts with phosphorus oxychloride, and the molar ratio of the two is controlled to be close to 1:1, and pentaerythritol is in excess to obtain intermediate 1; ; S2. At room temperature, nitrogen was introduced into a four-necked flask equipped with a stirrer, a thermometer and a fractionation device to remove the air in the device, and then intermediate 1 and 3-aminopropyltrimethoxysilane were added. The temperature of the reaction device was raised to 140°C, and the fractionation reaction was carried out for 2 hours. Then, the temperature was raised to 160°C and the fractionation reaction was carried out for 6 hours. During the reaction, a slight vacuum was maintained in the flask to separate methanol. After the reaction was completed, the temperature was lowered to room temperature, anhydrous ethanol was added, stirred and dispersed, and then filtered and dried to obtain intermediate 2. The ratio of intermediate 1 to 3-aminopropyltrimethoxysilane was 17.9 g:53.9 g. Using a solvent-free method, intermediate 1 reacts with 3-aminopropyltrimethoxysilane, and the molar ratio of the two is controlled to be close to 3:1 to obtain intermediate 2; ; S3. In a three-necked flask equipped with a thermometer and a stirring device, mix the intermediate 2 and N,N-dimethylformamide (DMF) and turn on the stirrer, add potassium carbonate (acid binding agent) and 1-chlorononane in sequence, control the reaction temperature to 65°C, keep the reaction warm for 4 hours, and after the reaction is completed, filter, remove the solvent by vacuum distillation, and vacuum dry to obtain intermediate 3; the ratio of the amount of intermediate 2, N,N-dimethylformamide, potassium carbonate, and 1-chlorononane is 62.3g:150mL:13.8g:16.2g; Potassium carbonate removes the hydrogen chloride generated by the reaction, accelerates the reaction, and intermediate 2 and 1-chlorononane undergo nucleophilic substitution to obtain intermediate 3; the specific reaction is shown below: ; S4. In a three-necked flask equipped with a thermometer and a stirring device, the intermediate 3, allyl chloride, potassium carbonate and N,N-dimethylformamide were mixed and stirred evenly, the reaction temperature was controlled to 70°C, and the reaction was kept warm for 6 hours. After the reaction was completed, it was filtered and purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:1), and the eluent was removed by rotary evaporation to obtain a synergistic flame retardant; the ratio of the intermediate 3, allyl chloride, potassium carbonate and N,N-dimethylformamide was 74.9g:7.6g:13.8g:150mL; Under the catalysis of potassium carbonate, intermediate 3 and allyl chloride undergo nucleophilic substitution to obtain a synergistic flame retardant; the structure of the synergistic flame retardant is shown below: ; The prepared synergistic flame retardant molecules contain silicon, nitrogen, caged phosphonate, long carbon chain and carbon-carbon double bond structure. Silicon will form -Si-O- or -Si-C- structure at high temperature. This structure can play a role of heat insulation and flame retardancy on the surface of the material, prevent the escape of combustion decomposition products, inhibit the thermal decomposition of polymer materials, and promote carbonization. The introduced nitrogen will decompose under heat during the combustion process, releasing non-combustible gases such as nitrogen, ammonia, and water vapor. These non-combustible gases can not only dilute the concentration of oxygen and combustible gases in the air, but also react with oxygen in the air to generate nitrogen, water and deep oxides, thereby consuming the surface of the material. Oxygen can achieve a good flame retardant effect; not only that, the introduced cage-like phosphonate structure is a phosphorus-based flame retardant with strong stability. It will promote the formation of a carbon layer and inhibit the release of smoke during combustion, and can synergize with silicon and nitrogen elements to significantly improve the flame retardant properties of the matrix; in addition, the introduced long carbon chain belongs to a methylene chain segment, which is a flexible chain segment, and can also improve the mechanical properties of the matrix, and can be interspersed in the macromolecular chain of the matrix to improve stability; finally, the introduced carbon-carbon double bond can be cross-linked with the PMMA matrix under the action of an initiator, making it difficult for the small molecule synergistic flame retardant to migrate and seep out of the matrix, further improving the stability of the synergistic flame retardant.

[0013] Beneficial effects of the present invention: 1. The PMMA sheet prepared by the present invention has modified nano-silicon dioxide added to the raw materials. Compared with ordinary nano-silicon dioxide, the surface hydrophobicity is stronger and the compatibility with the PMMA matrix is ​​better, which greatly enhances the wear resistance and mechanical properties of the PMMA sheet; 2. The prepared synergistic flame retardant molecules contain three elements: silicon, nitrogen and phosphorus. The three elements can work synergistically to significantly improve the flame retardancy of PMMA sheets. In addition, they can also enhance the mechanical properties of PMMA sheets and have good stability. Therefore, the PMMA sheet prepared by the present invention has good wear resistance, excellent mechanical properties, and stable and efficient flame retardancy, and has important application value in the field of acrylic sheet technology. DETAILED DESCRIPTION

[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] Embodiment 1

[0016] Preparation of synergistic flame retardants: S1. In a four-necked flask equipped with a constant pressure dropping funnel, a stirrer, a thermometer, a nitrogen inlet and outlet, a reflux condenser and a drying tube (connected to a hydrogen chloride absorption device), 15.1 g of pentaerythritol and 100 mL of tetrahydrofuran were added, nitrogen was introduced as a protective gas, and stirring was started. The temperature was slowly raised to 60°C, and 14.3 g of phosphorus oxychloride was added dropwise. The reaction began, a large amount of gas was released, and the reaction system gradually changed from a white turbid liquid to a transparent one, and then gradually became turbid again until the addition of phosphorus oxychloride was completed. The temperature was raised to 70°C, and the reaction was refluxed for 4 hours. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was washed with anhydrous ethanol and chloroform in sequence, and dried to obtain intermediate 1. S2. At room temperature, nitrogen was introduced into a four-necked flask equipped with a stirrer, a thermometer and a fractionation device to remove the air in the device, and then 17.9 g of intermediate 1 and 53.9 g of 3-aminopropyltrimethoxysilane were added. The temperature of the reaction device was raised to 140°C, and the fractionation reaction was carried out for 2 hours. The temperature was then raised to 160°C and the fractionation reaction was carried out for 6 hours. During the reaction, a slight vacuum was maintained in the flask to separate methanol. After the reaction was completed, the temperature was cooled to room temperature, anhydrous ethanol was added, stirred and dispersed, and then filtered and dried to obtain intermediate 2. S3, in a three-necked flask equipped with a thermometer and a stirring device, 62.3 g of intermediate 2 and 150 mL of N, N-dimethylformamide were mixed and the stirrer was turned on, and 13.8 g of potassium carbonate and 16.2 g of 1-chlorononane were added in sequence, and the reaction temperature was controlled to 65 ° C. The reaction was kept warm for 4 hours. After the reaction was completed, the reaction was filtered, the solvent was removed by distillation under reduced pressure, and vacuum drying was performed to obtain intermediate 3; S4. In a three-necked flask equipped with a thermometer and a stirring device, 74.9 g of intermediate 3, 7.6 g of allyl chloride, 13.8 g of potassium carbonate and 150 mL of N,N-dimethylformamide were mixed and stirred evenly. The reaction temperature was controlled to 70°C and the reaction was kept warm for 6 hours. After the reaction was completed, it was filtered and purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 5:1), and the eluent was removed by rotary evaporation to obtain a synergistic flame retardant.

[0017] Embodiment 2

[0018] Preparation of synergistic flame retardants: S1. In a four-necked flask equipped with a constant pressure dropping funnel, a stirrer, a thermometer, a nitrogen inlet and outlet, a reflux condenser and a drying tube (connected to a hydrogen chloride absorption device), 30.2 g of pentaerythritol and 200 mL of tetrahydrofuran were added, nitrogen was introduced as a protective gas, and stirring was started. The temperature was slowly raised to 60°C, and 28.6 g of phosphorus oxychloride was added dropwise. The reaction began, a large amount of gas was released, and the reaction system gradually changed from a white turbid liquid to a transparent liquid, and then gradually became turbid again until the addition of phosphorus oxychloride was completed. The temperature was raised to 70°C, and the reaction was refluxed for 4 hours. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was washed with anhydrous ethanol and chloroform in sequence, and dried to obtain intermediate 1; S2. At room temperature, nitrogen was introduced into a four-necked flask equipped with a stirrer, a thermometer and a fractionation device to remove the air in the device, and then 35.8 g of intermediate 1 and 107.8 g of 3-aminopropyltrimethoxysilane were added. The temperature of the reaction device was raised to 140°C, and the fractionation reaction was carried out for 2 hours. Then, the temperature was raised to 160°C and the fractionation reaction was carried out for 6 hours. During the reaction, a slight vacuum was maintained in the flask to separate methanol. After the reaction was completed, the temperature was cooled to room temperature, anhydrous ethanol was added, stirred and dispersed, and then filtered and dried to obtain intermediate 2. S3, in a three-necked flask equipped with a thermometer and a stirring device, 124.6 g of intermediate 2 and 300 mL of N, N-dimethylformamide were mixed and the stirrer was turned on, and 27.6 g of potassium carbonate and 32.4 g of 1-chlorononane were added in sequence, and the reaction temperature was controlled to 65 ° C. The reaction was kept warm for 4 hours. After the reaction was completed, the mixture was filtered, the solvent was removed by distillation under reduced pressure, and vacuum drying was performed to obtain intermediate 3; S4. In a three-necked flask equipped with a thermometer and a stirring device, 149.8 g of intermediate 3, 15.2 g of allyl chloride, 27.6 g of potassium carbonate and 300 mL of N,N-dimethylformamide were mixed and stirred evenly. The reaction temperature was controlled to 70°C and the reaction was kept warm for 6 hours. After the reaction was completed, it was filtered and purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 5:1), and the eluent was removed by rotary evaporation to obtain a synergistic flame retardant.

[0019] Embodiment 3

[0020] Preparation of modified nano-silica: Disperse 1 g of nano-silica in a three-necked flask containing 100 mL of ethanol-water solution. After ultrasonication for 10 min, add 3.4 g of γ-methacryloxypropyltrimethoxysilane, gradually raise the temperature to 60 °C, and react for 5 h under mechanical stirring. After the reaction is completed, cool to room temperature, filter and collect the residue, wash it three times with anhydrous ethanol, and dry it in a vacuum oven to obtain modified nano-silica.

[0021] Embodiment 4

[0022] First, 70g of methyl methacrylate, 8g of methyl acrylate, 5g of the synergistic flame retardant prepared in Example 1 and 10g of the modified nano-silica prepared in Example 3 were added to a reactor, and then 0.2g of dibenzoyl peroxide and 3g of zinc stearate were added. Stirring was started and the temperature was increased. When the raw materials in the reactor were fully mixed and boiled, the temperature was kept for 20 minutes, and the heating was stopped. The mixture was allowed to stand and cool to obtain a slurry. The slurry was injected into a sealed glass mold, the gas was removed, and the mixture was heated to 65°C. The polymerization reaction was carried out for 4h. After the reaction was completed, the mixture was annealed in an oven at 80°C for 2h. After cooling to room temperature, the mold was opened, and finally grinding and polishing were performed to obtain a flame-retardant PMMA sheet.

[0023] Embodiment 5

[0024] First, 75g of methyl methacrylate, 10g of methyl acrylate, 10g of the synergistic flame retardant prepared in Example 2 and 14g of the modified nano-silica prepared in Example 3 were added to a reactor, and then 0.3g of lauroyl peroxide and 4g of magnesium stearate were added. Stirring was started and the temperature was increased. When the raw materials in the reactor were fully mixed and boiled, the temperature was kept for 30 minutes, and the heating was stopped. The mixture was allowed to stand and cool to obtain a slurry. The slurry was injected into a sealed glass mold, the gas was removed, and the mixture was heated to 65°C. The polymerization reaction was carried out for 4h. After the reaction was completed, the mixture was annealed in an oven at 80°C for 3h. After cooling to room temperature, the mold was opened, and finally grinding and polishing were performed to obtain a flame-retardant PMMA sheet.

[0025] Embodiment 6

[0026] First, 80g of methyl methacrylate, 12g of methyl acrylate, 15g of the synergistic flame retardant prepared in Example 2 and 18g of the modified nano-silica prepared in Example 3 were added to a reactor, and then 0.4g of lauroyl peroxide and 5g of montan wax were added. Stirring was started and the temperature was increased. When the raw materials in the reactor were fully mixed and boiled, the temperature was kept for 40 minutes, and the heating was stopped. The mixture was allowed to stand and cool to obtain a slurry. The slurry was injected into a sealed glass mold, the gas was removed, and the mixture was heated to 65°C. The polymerization reaction was carried out for 4h. After the reaction was completed, the mixture was annealed in an oven at 80°C for 3h. After cooling to room temperature, the mold was opened, and finally the mold was ground and polished to obtain a flame-retardant PMMA sheet.

[0027] Comparative Example 1 The synergistic flame retardant in Example 6 was replaced by commercially available triphenyl phosphate flame retardant, and the remaining steps were the same as those in Example 6.

[0028] Comparative Example 2 Commercially available PMMA was used.

[0029] The transmittance was measured using the national standard GB / T2410-2008 "Determination of light transmittance and haze of transparent plastics"; The wear resistance is measured using the national standard GB 3960 "Test methods for sliding friction and wear of plastics"; The impact strength is measured using the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported plastic beams Part 1: Non-instrumented impact test"; The limiting oxygen index of the sample was measured according to the national standard GB / T 2406-2008 "Test method for combustion performance of plastics". After leaving Examples 4, 5, 6 and Comparative Example 1 at room temperature for 200 days, the limiting oxygen index was measured again.

[0030] The measured results are shown in the following table:

[0031] It can be seen from the above table that the PMMA sheet prepared in the embodiment of the present invention has excellent wear resistance, and because the embodiment adds a synergistic flame retardant, its mechanical properties and flame retardancy are higher than those of the control example, and the performance is stable, which has important application value in the field of acrylic board technology.

[0032] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0033] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a flame retardant PMMA sheet, characterized in that: The following steps are involved: First, methyl methacrylate, methyl acrylate, synergistic flame retardant and modified nano-silica are added to a reactor, and then an initiator and a release agent are added, stirring is started and the temperature is increased. When the raw materials in the reactor are fully mixed and boiled, the temperature is kept for 20-40 minutes, and the heating is stopped, and the mixture is allowed to stand and cool to obtain a slurry. The slurry is injected into a sealed glass mold, gas is removed, and a polymerization reaction is generated by heating. After the reaction is completed, an annealing treatment is performed in an oven, and the mold is opened after cooling to room temperature. Finally, the slurry is ground and polished to obtain a flame-retardant PMMA sheet. Wherein, the synergistic flame retardant is prepared by the following steps: S1. Add pentaerythritol and tetrahydrofuran into a four-necked flask, introduce nitrogen and start stirring, heat to 60°C, add phosphorus oxychloride dropwise, start the reaction, and continue until the addition of phosphorus oxychloride is complete. Heat to 70°C, reflux for 4 hours, and after the reaction is complete, distill under reduced pressure, wash, and dry to obtain intermediate 1. S2. At room temperature, nitrogen was introduced into a four-necked flask, and then intermediate 1 and 3-aminopropyltrimethoxysilane were added. After fractionation reaction at 140°C for 2 hours, the temperature was raised to 160°C and fractionation reaction was performed for 6 hours. During the reaction, a slight vacuum was maintained in the flask. After the reaction was completed, the temperature was lowered to room temperature, anhydrous ethanol was added, stirred and dispersed, and then filtered and dried to obtain intermediate 2. S3, mixing intermediate 2 and N,N-dimethylformamide and turning on the stirrer, adding potassium carbonate and 1-chlorononane in sequence, keeping the temperature at 65°C for 4 hours, and filtering, distilling under reduced pressure, and drying under vacuum to obtain intermediate 3; S4. Mix the intermediate 3, allyl chloride, potassium carbonate and N,N-dimethylformamide and stir evenly, keep warm at 70°C for 6 hours, and after the reaction is completed, filter, purify by column chromatography, and rotary evaporate to obtain a synergistic flame retardant.

2. The method for preparing a flame retardant PMMA sheet according to claim 1, characterized in that: In step S1, the ratio of pentaerythritol, tetrahydrofuran and phosphorus oxychloride is 15.1 g:100 mL:14.3 g.

3. The method for preparing a flame-retardant PMMA sheet according to claim 1, characterized in that: In step S2, the ratio of the amount of intermediate 1 to 3-aminopropyltrimethoxysilane used is 17.9 g:53.9 g.

4. The method for preparing a flame-retardant PMMA sheet according to claim 1, characterized in that: In step S3, the ratio of the amount of intermediate 2, N,N-dimethylformamide, potassium carbonate and 1-chlorononane is 62.3 g:150 mL:13.8 g:16.2 g.

5. The method for preparing a flame retardant PMMA sheet according to claim 1, characterized in that: In step S4, the ratio of the amount of intermediate 3, allyl chloride, potassium carbonate and N,N-dimethylformamide used is 74.9 g:7.6 g:13.8 g:150 mL.

6. The method for preparing a flame-retardant PMMA sheet according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 70-80 parts of methyl methacrylate, 8-12 parts of methyl acrylate, 5-15 parts of synergistic flame retardant, 10-18 parts of modified nano silicon dioxide, 0.2-0.4 parts of initiator, and 3-5 parts of release agent.

7. The method for preparing a flame-retardant PMMA sheet according to claim 1, characterized in that: The modified nano silicon dioxide is prepared by the following steps: Nano-silica was dispersed in a three-necked flask filled with ethanol aqueous solution. After ultrasonic treatment for 10 minutes, γ-methacryloxypropyltrimethoxysilane was added, and the temperature was gradually raised to 60°C. The mixture was reacted for 5 hours under mechanical stirring. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the residue was washed and dried to obtain modified nano-silica.

8. A flame retardant PMMA sheet, characterized in that: Prepared according to the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Silicon-containing expansive flame retardant and preparation method and application thereof

    CN102924521A

  • Preparation method of dodecyl silicate tri(phosphonic heterocyclic methyl) ester compound

    CN105294763A

  • Preparation method of dodecyl silicate cyclic phosphate ester compound as fire retardant

    CN105384779A

  • Safe flame-retardant acrylic plate and preparation method thereof

    CN114605765A

  • Waterproof crosslinked polyethylene sheath material for optical cable and preparation method of waterproof crosslinked polyethylene sheath material

    CN118184891A

Cited By

  • High-performance acrylic plate and manufacturing method thereof

    CN120623689A

  • Corrosion-resistant coating and application thereof in aluminum alloy heat exchange tube

    CN120775464A

  • Modified raw lacquer and preparation method thereof

    CN120888239A